Mutant p53 expression in fallopian tube epithelium drives cell migration. Issue 7 (11th April 2015) - Quartuccio, Suzanne M.; Karthikeyan, Subbulakshmi; Eddie, Sharon L.; Lantvit, Daniel D.; Ó hAinmhire, Eoghainín; Modi, Dimple A.; Wei, Jian‐Jun; Burdette, Joanna E.
<x xml:space="preserve">Abstract</x> Ovarian cancer is the fifth leading cause of cancer death among US women. Evidence supports the hypothesis that high‐grade serous ovarian cancers (HGSC) may originate in the distal end of the fallopian tube. Although a heterogeneous disease, 96% of HGSC contain mutations in p53. In addition, the "p53 signature, " or overexpression of p53 protein (usually associated with mutation), is a potential precursor lesion of fallopian tube derived HGSC suggesting an essential role for p53 mutation in early serous tumorigenesis. To further clarify p53‐mutation dependent effects on cells, murine oviductal epithelial cells (MOE) were stably transfected with a construct encoding for the R273H DNA binding domain mutation in p53, the most common mutation in HGSC. Mutation in p53 was not sufficient to transform MOE cells but did significantly increase cell migration. A similar p53 mutation in murine ovarian surface epithelium (MOSE), another potential progenitor cell for serous cancer, was not sufficient to transform the cells nor change migration suggesting tissue specific effects of p53 mutation. Microarray data confirmed expression changes of pro‐migratory genes in p53R273H MOE compared to parental cells, which could be reversed by suppressing Slug expression. Combining p53R273H with KRASG12V activation caused transformation of MOE into high‐grade sarcomatoid carcinoma when xenografted into nude mice. Elucidating the specific role of p53R273H in the fallopian tube will improve understanding of changes at the earliest stage of transformation. This information can help develop chemopreventative strategies to prevent the accumulation of additional mutations and reverse progression of the "p53 signature" thereby, improving survival rates.